2018
DOI: 10.4236/jbbs.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovariectomy and 17<i>β</i>-Estradiol Replacement on Dopamine D2 Receptors in Female Rats: Consequences on Sucrose, Alcohol, Water Intakes and Body Weight

Abstract: Background: Mechanisms underlying overeating-induced obesity in postmenopausal woman include functional lack of 17β-estradiol dysregulating dopamine D2 receptors, thereby inducing food addiction, glucose craving or alcohol dependence through reward circuitry. This study aimed at further understanding 17β-estradiol and dopamine D2 receptors interferences in the etiology of woman obesity. Method: Seventy-two Wistar female rats weighing 200 -205 g, individually-housed, were divided into non-ovariectomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…The use of E2, BR and SUL in the present experiments was related to our previous studies indicating that 17β-estradiol acted on two types of D2 receptors showing opposite functions to equilibrate energy intake vs. expenditure for weight set point regulation [20]. However, thiamine is the rotating wheel for body energy supply [4].…”
Section: Methodssupporting
confidence: 75%
See 4 more Smart Citations
“…The use of E2, BR and SUL in the present experiments was related to our previous studies indicating that 17β-estradiol acted on two types of D2 receptors showing opposite functions to equilibrate energy intake vs. expenditure for weight set point regulation [20]. However, thiamine is the rotating wheel for body energy supply [4].…”
Section: Methodssupporting
confidence: 75%
“…Conversely, D2L inhibited alcohol and food intakes, but induced specifically sugar consumption, thereby regulating blood glucose levels. D2L mediated the rapid metabolic effects of E2 [20]. Our studies indicated that 17β-estradiol acted on two types of D2 receptors showing opposite functions to equilibrate energy intake vs. expenditure for weight set point regulation [20].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations